Adição de ácido fítico na dieta de jundiá (Rhamdia quelen) - Costa, Letícia Lopes da (2018)
This work presents a study on the action of phytic acid in performance, metabolism and antioxidant activity of jundiá (Rhamdia quelen). Thirteen juveniles of jundúia averaging 7 ± 2.30g were randomly distributed in 20 polyethylene tanks of 70L (15 fish per tank) in a water recirculation system, and were fed for 50 days. Five diets were formulated, four with different levels of phytic acid (0.5% PA, 1.0% PA, 1.5% PA or 2.0% PA) and a control diet, that is, without the addition of phytic acid (0% PA). Four replicates were used for each set. The animals were fed three times daily to an apparent satiation. At the end of the experimental period, growth variables (final weight gain, specific growth rate, protein ratio and redundant food production) and carcass parameters (carcass yield, intestinal quotient, digestive index) were evaluated. hepatic-somatic and visceral fat). In addition, metabolic parameters (albumin, amino acids, total proteins, triglycerides, cholesterol, glucose) and hepatic parameters (protein, glycogen, glucose and ammonia) were selected. Also tested as activities of the enzymes trypsin, chymotrypsin, intestinal lipase and acid protease. No whole fish was analyzed at a centesimal (dry matter, mineral matter, crude protein and fat). The action of phytic acid as a pro-oxidant was tested with carbonyl and glutathione reductase proteins, in addition to the activity of the enzymes superoxide dismutase, catalase, glutathione peroxidase and glutathione S-transferase. Genes that received 0.5% AF had the visceral fat index and hepatic glycogen decreased. The 2.0% PA diet promotes the activity of the enzyme protease acid. The 1.5% of PA increased protein levels of any level of phytic acid in the diet, decreased fat concentration in whole fish composition. Fish that were fed 0.5% and 1.0% AF had lower carbonyl protein formation in both the liver and gills. Animals receiving 0.5% phytic acid in the diet had higher levels of GSH in the liver and gills, as well as greater activities of the GST and GPX enzymes (in the hepatic tissue). SOD and CAT activities in the liver were higher in fish receiving 0.5% and 1.0% PA. With this study it was possible to conclude that the presence of low concentrations of phytic acid in the diet of jundiá contributes to the improvement in fish quality and as an oxidative moderator.